Superconductivity at High Pressure in NbSe3 - Núñez Regueiro, M.; Mignot, J.-M.; Castello, D. (IOP Publishing, 1992)
Fil: Núñez Regueiro, M. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina